The Impact of Profit Growth, Company Size, and Investment Opportunity Set on Profit Quality (Study on Manufacturing Companies in the Food and Beverage Sub-Sector for the 2021-2024 period) - Adam Amirul Insan Subroto; Fitria Magdalena Suprapto; Rike Selviasari (LP2M IAIN Palopo, 2026)
This study has the aim to examine the effects of earnings growth, firm size, as well as investment opportunity set (IOS) on earnings quality in food and beverage manufacturing companies that are on the list of Indonesia Stock Exchange (IDX) throughout the 2021–2024 period. The hypotheses proposed are: (1) earnings growth has a significant effect on earnings quality; (2) firm size has a significant effect on earnings quality; (3) IOS has a significant effect on earnings quality; and (4) earnings growth, firm size, and IOS simultaneously affect earnings quality. This study uses a quantitative approach with secondary data from audited annual financial statements. Purposive sampling yielded a final sample of 21 companies (84 observations). Earnings quality is proxied by discretionary accruals using the Modified Jones model, earnings growth by the percentage change in net income, firm size by the natural logarithm of total assets, and IOS by the market-to-book value of equity (MBVE). Data were analyzed using multiple linear regression with classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). The results show that there is a significant negative effect of earnings growth on earnings quality (sig. = 0.000), while firm size (sig. = 0.279) and IOS (sig. = 0.108) do not have a significant partial effect. However, all three variables simultaneously affect earnings quality (sig. F = 0.000) with an Adjusted R² of 18.7%. These findings imply that earnings management in the post-pandemic recovery period is more strongly driven by changes in earnings performance than by company scale or growth opportunities. Companies are advised to strengthen internal control systems and transparent financial reporting to improve earnings quality, while investors should consider earnings growth trends as an indicator of earnings reliability. Keywords: Earnings Quality, Earnings Growth, Firm Size, Investment opportunity set, Discretionary Accruals